Biogenic Selenium Nanoparticles in Animal Nutrition: A Review - Svetlana Malyugina; Sylvie Skalickova; Jiri Skladanka; Petr Slama; Pavel Horky (Agriculture, 2021)
Selenium still represents a matter of debate in the scientific community. Bionanotechnology has introduced a whole new perspective on selenium use in animal nutrition. In recent years, attention has been focused on selenium nanoparticles prepared by chemical synthesis. Societal pressure directs research in a “greenway” that is more eco-friendly. Biogenic selenium nanoparticles thus represent a new space for research in the use of this new form of selenium in animal nutrition. Recent research shows that biogenic selenium nanoparticles have low toxicity, improve antioxidant status, and increase the body’s immune response. However, their benefits may be much greater, as numerous in vitro studies have shown. In addition, biogenic selenium nanoparticles possess antimicrobial, antifungal, and anticancer activities. Further research should answer questions on the use of biogenic selenium nanoparticles as a feed supplement in individual categories of livestock, and their safety in terms of long-term supplementation.